13C tracer analysis reveals the landscape of metabolic checkpoints in human CD8+ T cell differentiation and exhaustion - Kirchmair, Alexander; Nemati, Niloofar; Lamberti, Giorgia; Trefny, Marcel; Krogsdam, Anne; Siller, Anita; Hörtnagl, Paul; Schumacher, Petra; Sopper, Sieghart; Sandbichler, Adolf; Zippelius, Alfred; Ghesquière, Bart; et al. (Frontiers in Immunology, 2023)
Naïve T cells remain in an actively maintained state of quiescence until activation by antigenic signals, upon which they start to proliferate and generate effector cells to initiate a functional immune response. Metabolic reprogramming is essential to meet the biosynthetic demands of the differentiation process, and failure to do so can promote the development of hypofunctional exhausted T cells. Here we used 13 C metabolomics and transcriptomics to study the metabolism of CD8 + T cells in their complete course of differentiation from naïve over stem-like memory to effector cells. The quiescence of naïve T cells was evident in a profound suppression of glucose oxidation and a decreased expression of ENO1, downstream of which no glycolytic flux was detectable. Moreover, TCA cycle activity was low in naïve T cells and associated with a downregulation of SDH subunits. Upon stimulation and exit from quiescence, the initiation of cell growth and proliferation was accompanied by differential expression of metabolic enzymes and metabolic reprogramming towards aerobic glycolysis with high rates of nutrient uptake, respiration and lactate production. High flux in anabolic pathways imposed a strain on NADH homeostasis, which coincided with engagement of the proline cycle for mitochondrial redox shuttling. With acquisition of effector functions, cells increasingly relied on glycolysis as opposed to oxidative phosphorylation, which was, however, not linked to changes in mitochondrial abundance. We further investigated the metabolic phenotype of exhausted T cells, finding that their decreased effector function concurred with a reduction in mitochondrial metabolism, glycolysis and amino acid import, and an upregulation of quiescence-associated genes, TXNIP and KLF2, and the T cell suppressive metabolites succinate and itaconate. Overall, these results identify multiple metabolic features that regulate quiescence, proliferation and effector function, but also exhaustion of CD8 + T cells during differentiation. Thus, targeting these metabolic checkpoints may be a promising therapeutic strategy for both prevention of exhaustion and promotion of stemness of anti-tumor T cells.